Psychology of Failure: How Do Female Candidates Experience and Respond to Loss Aversion? A Phenomenological Study of the 2024 Indonesian General Election - Uswatun Hasanah; Imam Faisal Hamzah; Fatmah Bagis (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: This study examines the loss aversion experiences of female legislative candidates who were unsuccessful in Indonesia’s 2024 election, focusing on the emotional and psychological impact of electoral defeat. Methodology: Using a qualitative phenomenological method, ten female candidates who were not elected shared their experiences. Thematic analysis revealed significant financial, emotional, and social losses, amplified by gender-based stigma and societal expectations. Participants employed coping strategies such as reframing failure as a learning process and spiritual growth. Findings: Loss aversion the tendency to feel losses more deeply than equivalent gains—emerges as a key barrier for women in politics. Participants employed coping strategies such as reframing failure as a learning process and spiritual growth. Loss aversion strongly influenced their self-perception, motivation, and future political ambitions. Implications/Novel Contribution: The findings underscore the need for targeted support to help women navigate post-election challenges and remain engaged in politics. Enhanced backing from families, political parties, and broader society is crucial to building women’s resilience and promoting sustained political participation.